Evaluasi dan Perancangan Ulang User Interface menggunakan Metode Goal Directed Design (GDD) pada E-Learning SMKN 1 Sambeng Lamongan - A'an Choiril Anwar; Hanifah Muslimah Az-Zahra; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
SMKN 1 Sambeng is a state vocational school located in Lamongan Regency with 8 majors. This study involved 5 students as respondents to test scenario tasks and interviews and 20 students to fill out a questionnaire. In the initial data collection, it was concluded that when respondents accessed e-learning, they still experienced some difficulties in terms of language and the appearance of e-learning which was less attractive and informative. These problems make researchers aim to make improvements to the redesign of the e-learning user interface at SMKN 1 Sambeng. The method used when designing is Goal Directed Design (GDD) which focuses on user goals. There are 6 stages in the GDD method, namely research, modeling, requirements, framework, refinement and support. However, this research is only limited to the refinement stage, because the final result of this research will be a redesign of the user interface. From the interview results showed a positive response from the results of the redesign of the e-learning system, the task scenario test resulted in an effective travel time when the respondent was working on the given task, and from the distribution of the PMLQ questionnaire it increased from an average result of 6.89 and a standard deviation of 0, 91 compared to the initial data collection. From these results it can be interpreted that the redesign of the e-learning at SMKN 1 Sambeng Lamongan meets the needs of the respondents and is considered good by the respondents who represent the users of the e-learning system.